The Relationship Of Knowledge Of Public Mothers About Brestfeeding Techniques With The Event Of Blocked Nipples - Diana Sandra Dewi; Fatimah Nasution; Yesica Geovany Sianipar; Lisa Sibarani; Ingka Kristina Pangaribuan (Poltekkes Kemenkes Palembang, 2022)
Background: The puerperium (puerperium) is the period that begins after the placenta comes out and ends when the uterine organs return to their original state (before pregnancy) which lasts for about 6 weeks (Sulistyawati, 2017). Six weeks during the puerperium, a woman's body will experience changes, namely adaptation from the period of pregnancy and childbirth, until it gradually returns to its pre-pregnancy state (Bahiyatun, 2016). During the postpartum period, there is an activity that can bring its own happiness to the mother, namely breastfeeding where the mother feels that she has become a mother so that she can breastfeed her baby with her own breast milk which creates a sense of happiness for the mother herself.Methods: The design of this study used an analytical research design with a cross sectional approach in PMB Nurul Husna, Am.Keb, Sunggal District, Deli Serdang Regency, there are 47 postpartum mothers. The type of sampling used in this study is total sampling where the entire population is the sample in the study as many as 47 postpartum mothers. Results The results of the Chi-Square test are known to be Asymp (2-sided) 0.003 < 0.005, so based on the basis of the decision above, it can be seen that H0 is rejected and Ha is accepted. Then it can be seen that